Do Economic Linkages through FDI Lead to Institutional Change? Assessing Outcomes in Kazakhstan, Azerbaijan and Kyrgyzstan. Issue 4 (21st April 2019) - Vanderhill, Rachel; Joireman, Sandra F.; Tulepbayeva, Roza
Abstract: Foreign direct investment (FDI) can deliver benefits beyond the provision of capital, such as efficiency gains. We argue that the theorised positive effects of economic linkage are reduced when linkages are based on natural resources. Domestic elite coalitions supporting reform are also weaker in countries with extensive natural resources. Kazakhstan and Azerbaijan have high-value natural resources and significant FDI, making them most likely cases for reform. Kyrgyzstan is a contrasting case as it has few natural resources. We find that the institutional reforms we would anticipate because of linkages have not occurred and those that exist are often cosmetic.